Neoadjuvant chronomodulated capecitabine with radiotherapy in rectal cancer: a phase II brunch regimen study - Akgun, Zuleyha; Saglam, Sezer; Yucel, Serap; Gural, Zeynep; Balik, Emre; Cipe, Gokhan; Yildiz, ŞEYMA; YILDIZ, ŞEYMA; Kilickap, Sadettin; Okyar, Alper; Kaytan-Saglam, Esra (My University, 2014)
The aim of this study was to evaluate efficacy and safety of chronomodulated capecitabine administered according to a specific time schedule (Brunch Regimen: Breakfast and Lunch) as a part of neoadjuvant chemoradiation therapy in patients with locally advanced rectal cancer.